The Impact of Work-life Balance on Millennial’s Performance Mediated by Job Satisfaction - Nasser, Sandra (2022)
The primary aim of this research is to study the impact of work-life balance on millennial employees’ performance with the mediating role of job satisfaction. Millennials are individuals born between 1980 and 2000. These individuals are dominating the workplace which necessitates the importance of studying their work-life balance levels and how it can affect their satisfaction and performance to enhance the human and organizational outcomes. This study will give a clear review of the work-life balance constructs which include work personal life interference (WPLI), personal life interference with work (PLIW), and work personal life enrichment (WPLE) and how they affect millennial’s satisfaction and performance. For data collection purposes, an online questionnaire was sent to respondents working in private Lebanese corporations and 196 usable responses were gathered. In this study, SPSS statistical software was used for data analysis purposes and Hayes’s PROCESS was used to test the mediation effect. The research results confirmed that there is a negative relationship between WIPL and employee performance, a negative relationship between PLIW and employee performance, and a positive relationship between WPLE and employee performance and that job satisfaction fully mediates the relationship between each of the constructs and employee performance. Furthermore, this study will provide recommendations and implications that will aid organizations in retaining their talent through implementing successful work-life balance.